Posterior Reversible Encephalopathy Syndrome (PRES) in Children Undergoing Allogeneic Stem Cell Transplantation - Aleksandra Pivkova Veljanovska; Stojanoski, Zlate; Lazar Chadievski; Irina Panovska Stavridis; Sanja Trajkova; Lidija Cevreska; Borche Georgievski (Macedonian Academy of Sciences and Arts / Sciendo, 2019)
Posterior reversible encephalopathy syndrome (PRES) is one of the most serious complication after allogeneic stem cell transplantation in paediatric setting. It is most commonly reported as adverse event of immunosuppressive strategies during transplantation. We present a case of a 7 years old girl with myelodysplastic syndrome (MDS) treated with allogeneic stem cell transplantation (ASCT) at our department. Diagnosis of PRES was confirmed by imaging techniques during the first month after transplant and it was very likely connected with cyclosporine neurotoxicity. The aim of this article is to present our first experience in diagnosing and treating PRES in paediatric stem cell transplantation. Our experience showed that PRES is one of the reasons for higher transplant related mortality in children. Early prediction of factors contributing to PRES and closely monitoring of patient's vital signs, especially blood pressure, neurological status and vision are the main contributors for challenging the patient with another immunosuppressive agent that has less neurological toxicity. Still studies have to be initiated to confirm the influence of PRES on transplant outcome.
Keywords: PRES; complications; cyclosporine; outcome; stem cell transplantation